Salinity Tolerance in a Synthetic Allotetraploid Wheat (SlSlAA) Is Similar to Its Higher Tolerant Parent Aegilops longissima (SlSl) and Linked to Flavonoids Metabolism - Fu, Tiansi; Xu, Chenyang; Li, Hong; Wu, Xiaohan; Tang, Man; Xiao, Binbin; Lv, Ruili; Zhang, Zhibin; Gao, Xiang; Liu, Bao; Yang, Chunwu (Frontiers in Plant Science, 2022)
Allotetraploidization between A and S (closely related to B) genome species led to speciation of allotetraploid wheat (genome BBAA). However, the immediate metabolic outcomes and adaptive changes caused by the allotetraploidization event is poorly understood. Here, we investigated how allotetraploidization affected salinity tolerance using a synthetic allotetraploid wheat line (genome SlSlAA, labeled as 4x) and its Aegilops longissima (genome SlSl, labeled as SlSl) and Triticum urartu (AA genome, labeled as AA) parents. We found the degree of salinity tolerance of 4x was similar to its SlSl parent, and both were substantially more tolerant to salinity stress than AA. This suggests that the SlSl subgenome exerts a dominant effect for this trait in 4x. Compared with SlSl and 4x, the salinity-stressed AA plants did not accumulate higher concentration of Na+ in leaves but showed severer membrane peroxidation and accumulated higher concentration of ROS (H2O2 and O2.-) and less concentration of flavonoids, indicating that ROS metabolism plays a key role in salinity sensitivity. Exogenous flavonoid application to roots of AA plants significantly relieved salinity-caused injury. Our results suggest that the higher accumulation of flavonoids in SlSl may contribute to ROS scavenging and salinity tolerance, and these physiological properties were stably inherited to the nascent allotetraploid SlSlAA.